The Primary Reactions of Photosystems I and II of Algae and Higher Plants - Mathis,P; Rutherford,AW (New Comprehensive Biochemistry, 1987)
This chapter discusses the primary reactions of photosystems I and II of algae and higher plants. In photosynthetic organisms, the “primary reactions” fulfil the objective of converting the energy of light into a primary form of chemical energy which lasts for a time compatible with ordinary biochemical processes—that is, milliseconds. In these reactions, a rather large fraction, approximately 40%, of the photon energy is stored as chemical free energy. The primary reactions can be viewed from two major perspectives. Firstly, from a photochemical point of view: pigment molecules are excited to their lowest excited singlet state, which reacts in an electron transfer reaction, the first step of a process of charge separation. Secondly, from a biochemical point of view the reactions take place in highly organized complexes, the reaction centres, which are made up of several classes of molecules that cooperate in fulfilling complementary roles, such as: architectural support, light absorption, energy transfer and electron transfer. All oxygenic organisms, ranging from cyanobacteria to algae and higher plants, contain photosystem I (PS I) and PS II reaction centres, with only minor variations in spite of their large taxonomic and ecological diversity. © 1987, Elsevier B.V. All rights reserved.